Method of sliding mode control for ball – beam systems - Nguyen , Minh Tâm; Dao , Minh Tiến; Vu , Đình Đạt; Ho , Trọng Nguyễn; Nguyen , Minh Hoàng; Nguyen , Văn Đông Hải; Nguyen , Thị Oanh (Journal of Technical Education Science, 2016)
Nonlinear control algorithms are often used to control systems that have explicit dynamic equations. Out of such algorithms, sliding control mode is the most popular. The model in this paper is a ball -beam system - a popular model in control theory research. This paper presents a method of sliding mode control for ball - beam systems. The sliding mode control is designed to satisfy different set points of position of ball and guaranteed by mathematics. Simulation and experimental results at different working points prove that the sliding mode controller works well.